Calculation of possible damages that may be asked by the client who refused contract extension - Pistunov, Ihor (My University, 2023)
The authors of the article identified the problem of manufacturing enterprises in that a significant number of customers of their products refuses to extend the contract. This refusal is detrimental to the enterprise, since the funds have already been spent on designing the design, designing the location of the finished product, purchasing the necessary materials and components. Therefore, a method was developed to determine the extent of the potential loss that could give a manufacturing company a new client. For this purpose it is proposed to use statistics of pre-orders in which the client refused to extend the contract and did not pay the costs of the company that executed the orders for the manufacture and installation of the structure. Building a model of the level of damage that can be provided by the client, if he refuses the order, consists of stacking tables, which in addition to the level of damage includes the characteristics of the client company, such as the distance to the client, the age of the head of the client firm, the amount of the contract, date conclusion of the contract on production of a design, currency of balance of the customer.
Keywords: statistics of customer loss task; clustering; кластеризація; working capital; робочий капітал; economic-mathematical model; економіко-математична модель; separate functions